Exergaming-Based Dexterity Training in Persons With Parkinson Disease: A Pilot Feasibility Study. Issue 3 (July 2019) - van Beek, Judith J. W.; van Wegen, Erwin E. H.; Bohlhalter, Stephan; Vanbellingen, Tim
Abstract : Background and Purpose: Many individuals with Parkinson disease (PD) suffer from impaired dexterity, which impacts activities of daily living and quality of life. Exergaming, video game-based training with augmented virtual reality, may have value for improving function. The aim of the present pilot study was to comprehensively evaluate the feasibility of a dexterity training program using exergaming, in individuals with PD. Methods: Ten participants with PD (aged between 55 and 75 years, Hoehn and Yahr stages II-IV) trained over a period of 4 weeks, twice a week for 30 minutes. Baseline (T0) and postintervention (T1) assessments were done. Primary outcomes with respect to feasibility were the adherence rate, open-end questions, the level of participation (Pittsburgh Rehabilitation Participation Scale), and the usability (System Usability Scale). Dexterous function was measured with the Nine-Hole Peg Test and the Dexterity Questionnaire-24. Upper limb motor impairment was assessed by a modified version of the Movement Disorders Society Unified Parkinson's Disease Rating Scale III. Finally, quality of life was assessed by the 39-item Parkinson's Disease Questionnaire (PDQ-39). Results: Adherence rate was 99%, motivation increased significantly from 3.9 to 4.8 (Pittsburgh Rehabilitation Participation Scale, P = 0.03), and system usability of the exergaming system was acceptable to very good. Regarding potential efficacy, participants with impaired dexterity at T0 significantly improved in the Nine-Hole Peg Test and the PDQ-39. Discussions and Conclusions: The outcomes of this pilot study suggest that exergaming is feasible and has potential to improve dexterity in individuals with PD. Its efficacy should be investigated in a properly powered randomized controlled trial. Video Abstract available for more insights from the authors (see Supplemental Digital Content 1, available at: http://links.lww.com/JNPT/A270 ). Abstract : Supplemental Digital Content is Available in the Text.